2019
DOI: 10.1111/tbed.13110
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirainfection and shedding in cats in Thailand

Abstract: In Thailand, leptospirosis is considered an emerging disease in humans and animals. Many species can shed pathogenic Leptospira, including domestic cats (felis catus), which might be able to pose a risk to humans. There are no studies on Leptospira infections in cats in Thailand, but in other countries, it was demonstrated that cats can shed pathogenic Leptospira with high prevalences. The aims of this study were to evaluate whether outdoor cats in Thailand shed pathogenic Leptospira in their urine, and to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 24 publications
9
40
0
Order By: Relevance
“…The prevalence of urinary shedding from leptospiral DNA in the present research is consistent with that reported in previous studies in cats [6,7,14,15,18,19]. Our results also match with those obtained by Sprißler et al, 2018 (0.8%) [14] and Gomard et al, 2019 (0.6%) [8].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The prevalence of urinary shedding from leptospiral DNA in the present research is consistent with that reported in previous studies in cats [6,7,14,15,18,19]. Our results also match with those obtained by Sprißler et al, 2018 (0.8%) [14] and Gomard et al, 2019 (0.6%) [8].…”
Section: Discussionsupporting
confidence: 94%
“…A plausible explanation for this could be that either the animals had an acute infection with increasing antibody titers at the moment of sampling and no shedding of Leptospira DNA had occurred yet, or most likely that they were chronic carriers with falling or steady antibody titers and non-continuous Leptospira shedding in the urine. Similar findings have been previously described [14,15,18,20].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations